Modelos basados en grafos: Una aplicación al estudio del gasto de cruceristas en Uruguay - Juan Gabriel Brida; Florencia Santi\~naque; Bibiana Lanzilotta (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– This paper introduces the use of graphs in the analysis of the determinants of tourists' expenditure, providing an alternative approach to the methods usually employed. Graph-based analysis is applied to study the behavior of cruise passengers arriving at the ports of Montevideo and Punta del Este in Uruguay. The graphical representation allows to synthesize and visualize the relationships between the set of variables that characterize tourists or tourist groups and the determinants of their level of spending. The graph-based methodology is particularly suitable to represent the dependency relationships among variables (between adjacent nodes) and conditional independence (between non-adjacent nodes). For the empirical application, individual data from the surveys of cruise passengers corresponding to the cruise season between November 2014 and April 2015 in Uruguay are considered. The existence of dependencies between spending variables and other variables that may be of interest (sociodemographic, contextual, etc.) is studied. The exercise shows that the variables that better explain visitors' behavior are linked to the port of disembarkation and the expenditure. The results also show that socioeconomic variables are not directly linked to spending.
Keywords: C19; C21; D12; L83; 330; graph-based models; tourists' expenditure; cruise; Uruguay